Highly effective adsorption and passivation of Cd from wastewater and soil by MgO- and Fe3O4-loaded biochar nanocomposites - Ding, Hua; Liu, Jie; Li, Qibiao; Liu, Zhichen; Xia, Kai; Hu, Ling; Wu, Xiaoxu; Yan, Qian (Frontiers in Environmental Science, 2023)
Introduction: The application of Fe- (BC-Fe) and Mg-modified (BC-Mg) biochars for the remediation of heavy-metal-contaminated soil has become a research hotspot in recent years. It is critical to select suitable biochar for soil rejuvenation under the same pollution condition. Methods: In this study, the biochars were characterized by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM). In addition, the adsorption and passivation effects of BC-Fe and BC-Mg were comprehensively evaluated through batch adsorption experiments and soil incubation experiments, and the effects of Cd-contaminated soil on plant growth were also demonstrated by pot experiments. Results: SEM, FTIR, and XRD showed that MgO and Fe3O4 nanoparticles were successfully loaded on the biochar surface. The maximum adsorption efficiencies of BC-Fe and BC-Mg for Cd were 52.63 and 66.23 mg g−1, which was 9.05 and 7.19 times higher than that of the original biochar (7.32 mg g−1), respectively. Soil culture experiment showed that 5% BC-Fe and BC-Mg significantly reduced soil DTPA-Cd content by 38.86% and 50.85% at 120 days, respectively. In addition, BC-Fe and BC-Mg promoted the conversion of acid-soluble Cd to the oxidizable and residual states. Pot experiments revealed that BC-Fe and BC-Mg reduced the Cd content in shoots of the maize by 3.97 and 6.09 times, respectively, and both significantly increased the dry and fresh weights of the shoots and roots of the maize plants. Moreover, BC, BC-Fe, and BC-Mg provided nutrients required for plant growth to the soil and increased the activities of soil dehydrogenase, urease, and peroxidase. The adsorption–passivation mechanism of BC-Fe on Cd mainly included electrostatic attraction, while the adsorption–passivation mechanism of BC-Mg on Cd included precipitation and ion exchange. Discussion: Overall, the results showed that BC-Mg can be used as an efficient functional material for heavy-metal pollution remediation, and this study provided guidance on the selection of passivator materials for heavy-metal-contaminated soil remediation.